Lateral duodenal wall perforation due to plastic biliary stent migration: a case series of endoscopic closure - Bureau, Marc-Andre; Gkolfakis, Paraskevas; Blero, Daniel; Pezzullo, Martina; Devière, Jacques; Lemmers, Arnaud (Endoscopy International Open, 2020)
Background and study aims Lateral duodenal wall perforation by a migrated stent is a potential complication of biliary stenting. By systematic database revision, we identified a series of six patients with lateral duodenal wall perforation caused by a displaced plastic biliary stent that were treated with over-the-scope clip (OTSC) between January 1, 2014 and March 31, 2019. In this series, most cases were related to stenting of benign strictures with single or double stenting and with the use of stents longer than 12 cm. OTSC permitted perforation closure in all cases. Most patients had an excellent outcome and did not need any subsequent intervention. However, one patient, who presented with a more severe pneumoretroperitoneum on computed tomography scan, required laparotomy with peritoneal lavage and eventually died due to this complication. We conclude that endoscopic treatment of these perforations with OTSC could be an effective alternative to surgery in selected patients.